2022
DOI: 10.1039/d2cp01563c
|View full text |Cite
|
Sign up to set email alerts
|

Single ion free energy calculation in ASIC1: the importance of the HG loop

Abstract: Acid Sensing Ion Channels (ASICs) are one of the most studied channels of the Epithelial Sodium Channel/Degenerin (ENaC/DEG) superfamily. They are responsible for excitatory responses following acidification of the extracellular...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Taking advantage of statistical physics, MD simulations can also be used to calculate a permeation free energy profile and thus provide a detailed gating mechanism of ion permeation. The derived energy landscape helps to identify important restriction residues and energy barriers. Mhashal et al also studied cancer mutations found in genomic-wide tumor screens . MD simulations show that mutation (R252S) leads to wider upper and lower gates than wild type, facilitating ion and water permeation (Figure B).…”
Section: Membrane Protein Simulationsmentioning
confidence: 99%
“…Taking advantage of statistical physics, MD simulations can also be used to calculate a permeation free energy profile and thus provide a detailed gating mechanism of ion permeation. The derived energy landscape helps to identify important restriction residues and energy barriers. Mhashal et al also studied cancer mutations found in genomic-wide tumor screens . MD simulations show that mutation (R252S) leads to wider upper and lower gates than wild type, facilitating ion and water permeation (Figure B).…”
Section: Membrane Protein Simulationsmentioning
confidence: 99%
“…Notably, residues from the palm, ball, finger, and thumb domains combine to generate an acidic pocket in the extracellular domain, which is extremely negatively charged. Crucially, two pairs of carboxyl-carboxylate interactions that take place unusually close together between the side chains of aspartate or glutamate residues allow the molecule to sense pH [ 30 32 ].…”
Section: Asic1amentioning
confidence: 99%